STRATEGIC HUMAN RESOURCE MANAGEMENT IN RELATION WITH THE EMPLOYEE RESILIENCE OF EMPLOYEES OF PUBLIC SECTOR ORGANISATIONS - Sony Mary; Krishnaraj R (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Public sector organizations play a crucial role in providing essential services, implementing government policies, and promoting the welfare and well-being of citizens. They are funded through tax revenue and are accountable to the public and elected representatives. Strategic development, or simply sustainability has become more and more important recently. Conducting research on the relationship between strategic human resource management (SHRM) and employee resilience can provide valuable insights into the effectiveness of strategic HRM practices in promoting employee well-being and productivity. Research on the relationship between SHRM and employee resilience can have practical implications for organizations seeking to implement strategic HRM practices. This study is intended to find out the relationship between strategic human resource management and employee resilience and to suggest measures to enhance employee resilience through strategic HRM practices. A survey was conducted to measure the strategic HRM practices followed in an organization, and then examine the relationship between these practices and employee resilience. In addition unstructured interview with employee managers provided rich insights about the relationship between SHRM and employee resilience. About 300 employees and 60 employee mangers employed in four different public sector organisations were selected as the representative sample for study. A rating scale on strategic HRM practices followed in organisation was adopted for the initial survey and a resilience scale was used to collect data on employee resilience. The findings of research studies suggest that there is a positive relationship between strategic human resource management (SHRM) practices and employee resilience. Specifically, strategic HRM practices have been found to be positively related to employee well-being, job resources, social support, and psychological capital.